A Legal Appraisal of the Conceptualization of Environmental Protection - Phe, Ajeck Portia (Studies in Law and Justice, 2025)
This paper provides a critical legal appraisal of the conceptualization of environmental protection, examining its evolution, theoretical foundations, and implementation within national and international legal frameworks. Environmental protection has shifted from a reactive approach rooted in common law remedies to a more proactive, rights-based and sustainable development-oriented paradigm. The study explores key legal principles such as the precautionary principle, polluter pays, intergenerational equity, and public participation, and evaluates how these have shaped environmental legislation and policy. It further investigates the role of soft law, multilateral environmental agreements, and judicial activism in defining the legal contours of environmental protection. Challenges such as weak enforcement mechanisms, conflicts between economic development and ecological sustainability, and disparities in global environmental governance are also addressed. The paper argues for a more integrated and enforceable legal framework that balances ecological imperatives with socio-economic needs, advocating for the elevation of environmental rights within the broader context of human rights. Ultimately, the appraisal highlights the need for a robust legal conceptualization that responds effectively to contemporary environmental threats, including climate change and biodiversity loss.